New product development strategies for Hong Kong manufacturing industries - Yam, Richard C. M.; Chin, K. S.; Tang, Esther P. Y.
The new product development strategies for Hong Kong manufacturing industries were reviewed through surveys and interviews with special emphasis on the application and adoption of the Time-to-Market (TTM) concepts in Hong Kong. The study results imply that the majority of the Hong Kong manufacturers need to go through a substantial strategic change in order to sustain their competitiveness in the rapidly changing world market. The corporate focus should be changed from the low-cost manufacturing biased to the high quality, customer-based and marketing/technology integrative emphasis.
Keywords: Time-to-market (TTM) concept; Product development strategies